Optimal Feedback Control of Vehicle Vibration with Eight Degrees of Freedom - Ali Hemati; Mehdi Tajdari; Ahmadreza Khoogar (Institute of Advanced Engineering and Science, 2014)
In this paper the unfavorable body vibration of vehicles is compensated using direct feedback signals in an optimized manner. The parameter - optimization problem was gained through the second method of Liapunov. Moving vehicles bear unfavorable body vibration, especially in bumpy roads. Therefore, active control of this vibration seems attractive. Vertical vibration of the vehicle affects the driver's performance. In this paper an eight degrees of freedom dynamic vibration model of a general vehicle are developed through the designation of a closed-loop control system. A control system has been designed with efficient response which computes the feedback gains using the second method of Liapunov and it has been proven that appropriate comparison is obtained with this controller.